Chlorinated very short-lived substances offset the long-term reduction of inorganic stratospheric chlorine - Kimberlee Dubé; Susann Tegtmeier; Adam Bourassa; Johannes C. Laube; Andreas Engel; Laura N. Saunders; Kaley A. Walker; Ryan Hossaini; Ewa M. Bednarz (Communications Earth & Environment)
Abstract Over the past few decades, a reduction in chlorinated long-lived ozone-depleting substance emissions due to the regulations imposed by the Montreal Protocol has led to a global decrease in stratospheric chlorine. At the same time, emissions of chlorinated Very Short-Lived Substances, which are unregulated, have increased. Here we show that observed changes of inorganic stratospheric chlorine are inconsistent with changes in the tropospheric abundances of long-lived ozone-depleting substances. Satellite observations of stratospheric chlorine species from the Atmospheric Chemistry Experiment—Fourier Transform Spectrometer during 2004–2020 reveal that the observed decrease in inorganic stratospheric chlorine is 25%–30% smaller than expected based on trends of long-lived ozone-depleting substances alone. At mid-latitudes in the lower stratosphere, this can be explained by the chlorinated Very Short-Lived Substances increase, which offsets the long-term reduction of stratospheric chlorine by up to 30%.